2018
DOI: 10.1017/s1479409817000581
|View full text |Cite
|
Sign up to set email alerts
|

Notions of the Universal and Spiritual in Percy Grainger’s Early British Folk-Song Settings

Abstract: Between 1905 and 1908 Percy Grainger made a major contribution to the corpus of British folk-song, collecting melodies and words of ballads, shanties and work songs, and devoting himself not just to the faithful capture of pitch and rhythm, but also the nuances of performance, with his pioneering use of the phonograph. These folk-songs became for Grainger a wellspring of compositional inspiration to which he returned time and time again. Yet while he was still a student in Frankfurt, Grainger had been making s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Cāulukyan ruler Bhīma II possessed ships that sailed to Sindh, which clearly illustrates the point of kṣatriyas participating in commercial activities. 34 According to another incident, Kṣemarāja, one of the sons of Yogarāja Chāvaḍā, reported that several ships were storm-stayed at Prabhāsa or Somanātha. 35 The ships had 10,000 horses, elephants, and millions of money and treasure.…”
mentioning
confidence: 99%
“…Cāulukyan ruler Bhīma II possessed ships that sailed to Sindh, which clearly illustrates the point of kṣatriyas participating in commercial activities. 34 According to another incident, Kṣemarāja, one of the sons of Yogarāja Chāvaḍā, reported that several ships were storm-stayed at Prabhāsa or Somanātha. 35 The ships had 10,000 horses, elephants, and millions of money and treasure.…”
mentioning
confidence: 99%